Kinerja pengawas dalam pelaksanaan supervisi pendidikan pada sekolah dasar negeri gugus III Kotagede UPT wilayah timur Kota Yogyakarta - Sukarno Sukarno; Samidjo Samidjo (Universitas Sarjanawiyata Tamansiswa, 2015)
This study aims to reveal the planning, implementation and supervision results conducted by the superintendent of schools in order to improve the performance of principals and teachers in primary schools. This research is a descriptive study subjects research supervisors, principals and teachers throughout the cluster III timur. While Kotagede the city of Yogyakarta region in the object of this study is the performance of schools in the district area superintendent Kotagede yogyakarta.Data city schools superintendent drawn about the performance of several schools in the cluster III Kotagede namely: SDN Kotagede I , SDN Kotagede IV, SDN Kotagede V, SDN Dalem , and SDN baluwarti. Taking schools as research sites that have variations: their location, number of students, school conditions and school achievement. The results of this descriptive analysis shows that in terms of planning, monitoring public primary school education offices throughout the cluster III Kota Gede Yogyakarta, before carrying out supervision has drawn up an action plan that includes schedule supervision, academic supervision and supervision instrument managerial. Preparation of schedule implemented at the beginning of the semester by the supervisor. As for the schools under its assistance is determined by monitoring the implementation of the terms of the task letter .Refer to supervision activities, school superintendent has been carrying out supervision activities, but there are some activities to supervise the implementation of the existing school which was aborted by the supervisor, it is because: (1) lack of time activities in conjunction with the education department to schedule a visit to the school supervision. (2) the sudden task of agencies and in conjunction with a scheduled visit to the school so that the supervisor must complete the first task of the department. The results that have been obtained as a form of performance that improved performance supervisory principal, which is indicated by an increase school quality in the form of school management. While improving the performance of teachers in the form of teachers’ ability to design programs of learning, use of learning strategies, conducting evaluations, carrying out the analysis of the evaluation results and implement improvements as well as enrichment lessons for students, thus increasing learning achievement.